Balancing work and life: A study of work effects on the quality of women’s life - AL-Dhaheri, Fatima Saif; Al-Othman, Hussain (Al-Adab Journal, 2021)
This study aimed to know the impact of a woman’s work on her quality of life, to identify how a working woman achieves a balance between her work and her life, to uncover aspects of the impact of work on a woman’s life, and to uncover the challenges that prevent achieving this balance. The researcher used the descriptive and analytical approach for its ability to describe the study variables with the required accuracy, where the study was applied to a random sample of women working in governmental and private Emirati institutions, and their number reached (400) women, and the questionnaire was used and distributed to them, then the data were collected and entered into a program SPSS to be analyzed. The study found that there is a statistically significant discrepancy with an F value of (63.482), which is a statistically significant value at the level of 0.05, in the opinions of working women about aspects of the impact of work on the lives of Emirati women, as the views of the participants differed in terms of support and acceptance among the average and higher. However, in terms of ways for the working woman to achieve a balance between her work and her life, the results showed that there is a statistically significant discrepancy with a value of F (43.033), which is a statistically significant value at the level of 0.05, in women’s opinions about it between the average and the high as well, while the results showed in the last part that there is a statistically significant discrepancy with an F value of (39,653), which is a statistically significant value at the level of 0.05, in the views of women about the challenges that prevent the working woman from achieving a balance between her work and her life, between medium and low. In the end, the results revealed that the effect of the study variables, including age, education, the nature of the work sector, the number of daily working hours, the duration of marriage, and the presence of children with a woman, is statistically significant in both aspects of the impact of work on her life, and in the ways the working woman achieves balance between her work and her life, as well as the challenges that prevent working women from achieving a balance between her work and her life.